Effect of curing regimes on hardened performance of concrete containing slag cement. (30th June 2019) - Amini, Kamran; Ceylan, Halil; Taylor, Peter C.
Highlights: Curing regime is a vital factor affecting concrete hardened performance. Correlation between air-void system and salt-scaling resistance is negligible. Salt scaling is mainly affected by sorptivity and surface hardness of the concrete. Lower resistance of a slag concrete to salt scaling is not a physical issue. Abstract: This paper is focused on evaluating the impact of curing on concrete performance, and correlating hardened performance to salt-scaling resistance of concrete. The performance of the mixtures was determined through air-void system, sorptivity, and abrasion tests. A total of seven different curing regimes were applied to mixtures made with different binary systems containing 0%, 20%, 40%, and 60% slag cement. The results obtained showed that curing affects salt-scaling potential by changing sorptivity and abrasion resistance of the mixtures. While slag-cement replacement reduced the scaling resistance of the mixtures, a replacement of up to 40% improved the mechanical and transport properties. In addition, no correlation was observed between salt scaling and the air-void system.